The Effect of CSR, Company Size, and Sales Growth on Profitability of Financial Sector Companies in Indonesia - Lucia Rita Indrawati; Retnosari; Adella Vania Frimasika (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The financial sector in Indonesia faces challenges in maintaining profitability while fulfilling social responsibilities. This study investigates the impact of corporate social responsibility, company size, and sales growth on the profitability of financial companies listed on the Indonesia Stock Exchange. The research aims to analyze how these factors influence profitability, measured by return on assets, using data from 110 financial companies over the period 2021 to 2024. A quantitative approach with multiple linear regression was employed to analyze secondary data from financial and sustainability reports. The findings reveal that company size and sales growth have a significant positive effect on profitability, while corporate social responsibility shows no significant impact. Larger companies benefit from cost efficiencies, and higher sales growth reflects successful market expansion. These results suggest that financial institutions should prioritize operational scale and innovative products to enhance profitability, while strategically integrating social initiatives to maximize their impact. This study provides insights for stakeholders to develop strategies that balance profitability and social responsibility in Indonesia’s competitive financial landscape.